Emergence of eravacycline heteroresistance in carbapenem-resistant Acinetobacter baumannii isolates in China - Li, Yi-tan; Chen, Xian-di; Guo, Ying-yi; Lin, Shan-wen; Wang, Ming-zhen; Xu, Jian-bo; Wang, Xiao-hu; He, Guo-hua; Tan, Xi-xi; Zhuo, Chao; Lin, Zhi-wei (Frontiers in Cellular and Infection Microbiology, 2024)
Carbapenem-resistant Acinetobacter baumannii (CRAB) is resistant to almost all antibiotics. Eravacycline, a newer treatment option, has the potential to treat CRAB infections, however, the mechanism by which CRAB isolates develop resistance to eravacycline has yet to be clarified. This study sought to investigate the features and mechanisms of eravacycline heteroresistance among CRAB clinical isolates. A total of 287 isolates were collected in China from 2020 to 2022. The minimum inhibitory concentration (MIC) of eravacycline and other clinically available agents against A. baumannii were determined using broth microdilution. The frequency of eravacycline heteroresistance was determined by population analysis profiling (PAP). Mutations and expression levels of resistance genes in heteroresistant isolates were determined by polymerase chain reaction (PCR) and quantitative real-time PCR (qRT-PCR), respectively. Antisense RNA silencing was used to validate the function of eravacycline heteroresistant candidate genes. Twenty-five eravacycline heteroresistant isolates (17.36%) were detected among 144 CRAB isolates with eravacycline MIC values ≤4 mg/L while no eravacycline heteroresistant strains were detected in carbapenemsusceptible A. baumannii (CSAB) isolates. All eravacycline heteroresistant strains contained OXA-23 carbapenemase and the predominant multilocus sequence typing (MLST) was ST208 (72%). Cross-resistance was observed between eravacycline, tigecycline, and levofloxacin in the resistant subpopulations. The addition of efflux pump inhibitors significantly reduced the eravacycline MIC in resistant subpopulations and weakened the formation of eravacycline heteroresistance in CRAB isolates. The expression levels of adeABC and adeRS were significantly higher in resistant subpopulations than in eravacycline heteroresistant parental strains (P < 0.05). An ISAba1 insertion in the adeS gene was identified in 40% (10/25) of the resistant subpopulations. Decreasing the expression of adeABC or adeRS by antisense RNA silencing significantly inhibited eravacycline heteroresistance. In conclusion, this study identified the emergence of eravacycline heteroresistance in CRAB isolates in China, which is associated with high expression of AdeABC and AdeRS.